P172 NLRP3 inflammasome-mediated pyroptosis aggravates the airway inflammation in toluene diisocyanate-induced asthmatic mice. (March 2019) - Zhuang, J; He, Y; Cui, H; Sun, E; ,; Yang, Fangyuan; He, Juan; Zhai, Zeqing; Zhao, Haijin; Zhao, Wenqu
Abstract : Career situation of first and presenting author: Young investigator. Introduction: NLRP3 inflammasome-mediated pyroptosis is a highly inflammatory event. This cell death process is characterized by cell explosion and IL-1β release. 1 Our previous data have revealed that NLRP3 inflammasome-mediated pyroptosis plays an essential role in the pathogenesis of collagen-induced arthritis mice and lupus-like mice . While blockade of NLRP3 inflammasome-mediated pyroptosis alleviates the inflammation and organ damage in these autoimmune mice models. Objectives: Interesting, Toluene diisocyanate(TDI), the most common organic compound causing occupational asthma, has been proven to drive bronchial epithelium damage and IL-1β production in patients with TDI-induced asthma. Therefore, in this study, we investigated whether NLRP3 inflammasome-mediated pyroptosis was involved in bronchial epithelial injury and airway inflammation in TDI-induced asthma. Methods: In vitro, 16HBEs (a human bronchial epithelial cell line) were stimulated with TDI. Then the cell death form was identified. In vivo, TDI-induced asthmatic mice were established after sensitization and challenge with TDI. After treatment with the NLRP3 inflammasome specific inhibitor, the airway hyperresponsiveness (AHR) and airway inflammation in asthmatic mice were assessed. Results: Here we found that TDI induced 16HBEs pyroptosis in a time and dose-dependent manner, as evidenced by the increased ratio of caspase-1 + PI + cells and the enhanced levels of LDH and IL-1β. Importantly, the NLRP3 inflammasome specific inhibitor significantly blocked TDI-induced pyroptosis. In TDI-induced asthmatic mice, NLRP3 inflammasome inhibitor attenuated AHR and airway inflammatory infiltration by inhibiting the activation of caspase-1 and the cleavage of pyroptotic executioner GSDMD in the lungs. Moreover, NLRP3 inflammasome inhibitor decreased the levels of IL-1β in the plasma and bronchoalveolar lavage fluid (BALF), accompanied by lower level of IgE in the plasma and Th2-related cytokines in the BALF. Conclusions: Our data demonstrated for the first time that bronchial epithelial pyroptosis was critical for TDI-induced asthma pathogenesis via the activation of NLRP3 inflammasome and the cleavage of GSDMD. Inhibition of NLRP3 inflammasome-mediated pyroptosis may be a valuable therapeutic strategy for TDI-induced asthma. Reference: Shi J, et al . Cleavage of GSDMD by inflammatory caspases determines pyroptotic cell death. Nature 2015. Acknowledgements: This work was supported by National Natural Science Foundation of China (81501417, 81671623, 81873880), Medical Scientific Research Foundation of Guangdong Province, China (A2016492) and Science and Technology Planning Project of Tianhe Distric, Guangzhou City (201504KW037). Jian Zhuang and Yi He contributed equally as co-first authors. Haiyan Cui and Erwei Sun are corresponding authors. Disclosure of Interest: None declared.